Root Exudates Metabolic Profiling Suggests Distinct Defense Mechanisms Between Resistant and Susceptible Tobacco Cultivars Against Black Shank Disease - Zhang, Chengsheng; Feng, Chao; Zheng, Yanfen; Wang, Jing; Wang, Fenglong (Frontiers in Plant Science, 2020)
There is increasing evidence that root exudates play important roles in plant disease resistance. Black shank, caused by Phytophthora nicotianae, is a destructive soil-borne disease in tobacco (Nicotiana tabacum L.). The aim of the present study was to investigate the activity and composition of the root exudates from resistant and susceptible tobacco cultivars. The root exudates of the resistant cultivar Gexin 3 showed inhibitory activity against P. nicotianae, while the exudates of susceptible cultivar Xiaohuangjin 1025 exhibited a stimulating effect. Metabolic profiling using liquid chromatography/electrospray ionization-quadrupole-time-of-flight mass spectrometry depicted differing metabolic patterns of root exudates between Gexin 3 and Xiaohuangjin 1025. The activity and composition of root exudates was altered by P. nicotianae inoculation. Multivariate analysis showed that root exudates (including organic acids, alkaloids, fatty acids, and esters) were different between the two varieties. The defense substances in root exudates, such as tartaric acid, ferulic acid, and lauric acid, may represent a pre-infection prevention strategy for tobacco. Phenylpropanoid as well as inducers of salicylic acid, fatty acids, 6-hydroxyhexanoic acid, and hydrojasmonate may be involved in tobacco defense responses. Compared to the susceptible cultivar, the roots of the resistant cultivar exhibited high enzyme activities of phenylalanine ammonia-lyase, cinnamate-4-hydroxylase and 4-coumarate-CoA ligase, which may prompt the synthesis and secretion of phenylpropanoids. Our results indicated that the root exudates not only provide a pre-infection prevention strategy by exuding antimicrobial substances, but also increase tobacco disease resistance by eliciting plant defense responses. In addition, some defense compounds as well as compounds that play a role in inducing plant defense responses, showed potential for disease control application. This study provides an insight into possible disease resistance mechanisms of root exudates, and attempts the beneficial utilization of these secondary metabolites of plants.